Perioperative Blood Transfusion and Occurrence of Surgical Site Infection: An Integrative Review. (27th November 2019) - Mantoani, Camila Cristina; Margatho, Amanda Salles; Dantas, Rosana Aparecida Spadoti; Galvão, Cristina Maria; de Campos Pereira Silveira, Renata Cristina
ABSTRACT: The aim of this integrative review was to locate, assess, and synthesize available evidence of the relationship between perioperative allogeneic blood transfusion and the occurrence of surgical site infection among adult patients undergoing elective surgery. After a comprehensive search of relevant databases and a review of the studies this yielded, we used a validated instrument to extract data from the 25 studies in our final sample. The clinical and surgical variables that were significantly and more frequently associated with the occurrence of surgical site infection among patients who received blood transfusions during the perioperative period were female sex, older age, and higher body mass index. Our findings indicate a lack of consensus on the hemoglobin levels that indicate a blood transfusion is necessary.